Objective Structured Clinical Examinations 10 Steps to Planning and Implementing OSCEs and Other Standardized Patient Exercises - Zabar, Sondra; Kachur, Elizabeth; Kalet, Adina; Hanley, Kathleen; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Objective structured clinical examinations (OSCEs) and other exercises that utilize standardized patients (SPs) can simulate actual clinician-patient encounters with great impact. They are one of the most effective methods for training and assessing competencies across undergraduate, (post)graduate, and continuing health professions education. However, organizing such programs requires strong leadership and the collaboration of many key individuals for planning and implementation. This book, Objective Structured Clinical Exams: 10 Steps to Planning and Implementing OSCEs and other Standardized Patient Exercises, serves as a comprehensive how-to manual and addresses the need for best practice guidelines. It contains a review of relevant literature, pointers for designing OSCE cases, tips on recruiting and training standardized patients, and it describes innovative uses of standardized patients for remediation and assessment in clinical settings. Charts, graphs, and sample forms are included to make this a singular resource for any educator interested in creating or improving OSCEs and other standardized patient programs.
PART 1: INTRODUCTION -- Definitions -- Why use SPs and OSCEs? -- History and current use -- How can Standardized Patients and OSCEs satisfy national competency guidelines? -- PART TWO: TEN STEPS FOR ORGANIZING OSCEs AND OTHER SP EXERCISES -- Assemble a team -- Agree on goals and scope and make a plan -- Establish a blueprint -- Develop cases and stations -- Create rating forms -- Recruit and train standardized patients (SPs) -- Recruit and train raters -- Manage logistics and implement the program -- Analyze and report data -- Develop a case library -- PART THREE: ADDITIONAL APPLICATIONS OF STANDARDIZED PATIENTS -- Use of standardized patients for remediation -- GOSCEs (Group Observed Structured Clinical Experiences) -- OSTEs (Observed Structured Teaching Exams) -- Unnanounced Standardized Patients - "The Secret Shopper" -- APPENDICES -- Medical error disclosure case -- SP medical error rating form -- Faculty medical error rating form -- Resident evaluation of OSCE experience -- Faculty evaluation of OSCE experience -- SP evaluation of OSCE experience -- Rotation schedule.-.
Keywords: Medicine; Health administration; Internal medicine; Medicine & Public Health; Internal Medicine; Health Administration; Electronic books